Reliability of finger strength assessment methods in climbing: a systematic review - Pérez-Cordero, Jorge; Jerez-Mayorga, Daniel; Rodríguez-Perea, Ángela; Soto García, Diego (Frontiers in Sports and Active Living, 2025)
BackgroundThis systematic review examined the reliability of finger flexor strength assessments in climbers, addressing the absence of a prior synthesis on this topic. The work is timely given sport climbing's inclusion in the Olympic Games and the growing focus on sport-specific performance diagnostics. Fifteen studies, comprising 747 participants (sample sizes 13–244) with varying skill levels, were included.MethodsConducted in accordance with PRISMA guidelines and based on a protocol registered in INPLASY, the search encompassed Web of Science, PubMed, Scopus, and SportDiscus, using MeSH terms and relevant keywords. Eligible studies involved climbers, employed a test–retest design, reported strength variables, and provided reliability parameters (ICC). Methodological quality was evaluated with the Critical Appraisal Tool (CAT) and the Quality Appraisal for Reliability Studies (QAREL).ResultsFourteen studies reported high reliability (ICC > 0.75) in at least one assessment, while 12 studies showed very high ICC values for maximum isometric finger strength (MIFS) tests (median range: 0.85–0.99), indicating good to excellent reliability. Most studies (n = 12) used varied grip types and edge depths (6–60 mm). Bilateral measurements were included in eight studies, though five used non-simultaneous protocols, potentially limiting ecological validity.DiscussionAdoption of advanced measurement technologies and harmonized protocols is recommended to enhance comparability, practical relevance, and training effectiveness. These measures may also contribute to greater standardization in research designs and facilitate translation of findings into applied settings.ConclusionMIFS assessments with fixed-depth edges of approximately 20–23 mm consistently demonstrate high reliability and should be prioritized for standardized monitoring in both applied and research contexts.Systematic Review Registrationhttps://inplasy.com/inplasy-2024-10-0070, identifier INPLASY2024100070.